Land Disputes in Pakel Village from the Perspective of Agrarian Reform (Indonesian Journal of Agrarian Law, 2026)
This study analyzes the land dispute in Pakel Village, Licin District, Banyuwangi Regency, through the lens of agrarian reform following the enactment of Banyuwangi Regency Regional Regulation No. 2 of 2024 concerning the 2024–2044 Regional Spatial Plan. The dispute arises from the classification of the contested area as a plantation zone, which may reinforce the legal standing of the company's Right to Cultivate (Hak Guna Usaha/HGU), despite the existence of historical claims and longstanding community control over the land. This research aims to assess whether the spatial planning policy incorporates considerations of agrarian justice and equitable land management or instead contributes to the persistence of structural inequalities in land tenure. Employing normative legal research, the study adopts statutory, conceptual, and case approaches, with particular emphasis on Judgment No. 181/Pdt.G/2024/PN Banyuwangi. Data were obtained through literature review, examination of legal documents, and interviews. The findings reveal that, although Regional Regulation No. 2 of 2024 is formally consistent with national spatial planning frameworks, it has not adequately accommodated agrarian reform principles or recognized the historical dimensions of land tenure in Pakel Village. The designation of plantation areas within the disputed territory may strengthen the position of HGU holders while limiting opportunities for local communities to obtain formal recognition of their land rights. Accordingly, this study highlights the need for participatory and equitable mechanisms, including mediation, spatial policy evaluation, and the reinforcement of agrarian reform initiatives in resolving agrarian conflicts in Pakel Village.